Impact of mechatronic in medicine - Elizabeth Larrondo Pons; Gustavo Cervantes Montero; Angel Sánchez Roca (Centro Provincial de Información de Ciencias Médicas, 2018)
A literature review was carried out to determine the impact of mechatronic in the health sector. Its development was evaluated from the point of view of different investigators, which has allowed its insertion in this sector. It was also proven that  robotics and digital processing of images and signs have higher incidence in medicine. Also, an analysis of mechatronic applied to this science was carried out, which demonstrated that the surgical and therapeutical areas are the most favored and receive nourishment through innovative techniques that are more reliable and less invasive for the patient.